2019
DOI: 10.1242/jeb.178749
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic noise and the bioacoustics of terrestrial invertebrates

Abstract: Anthropogenic noise is an important issue of environmental concern owing to its wide-ranging effects on the physiology, behavior and ecology of animals. To date, research has focused on the impacts of far-field airborne noise (i.e. pressure waves) on vertebrates, with few exceptions. However, invertebrates and the other acoustic modalities they rely on, primarily near-field airborne and substrate-borne sound (i.e. particle motion and vibrations, respectively) have received little attention. Here, we review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 160 publications
(181 reference statements)
2
29
0
Order By: Relevance
“…at distances less than a few tens of centimetres from the source. This hypothesis is consistent with the close-range communication well described in terrestrial arthropods (Raboin and Elias, 2019). Here, we did not measure or model the acoustic particle motion field in the behavioural area as this was out of the scope of the study.…”
Section: Discussionsupporting
confidence: 77%
“…at distances less than a few tens of centimetres from the source. This hypothesis is consistent with the close-range communication well described in terrestrial arthropods (Raboin and Elias, 2019). Here, we did not measure or model the acoustic particle motion field in the behavioural area as this was out of the scope of the study.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have suggested that air particle movement is probably used by many insects and arthropods (Barth, Humphrey, Wastl, Halbritter, & Brittinger, 1995;Cator, Ng'Habi, Hoy, & Harrington, 2010;Klopsch, Kuhlmann, & Barth, 2013;Lapshin & Vorontsov, 2017;Santer & Hebets, 2008;Santer & Hebets, 2011;Shimozawa & Kanou, 1984). Some argue that the ability of animals to use air particle movements to guide behaviour has been dramatically underestimated (Barth & H€ oller, 1999;Bathellier, Steinmann, Barth, & Casas, 2012;Klopsch et al, 2013;Raboin & Elias, 2019;Shamble et al, 2016). In line with this suggestion, Rundus et al (2010) previously suggested that the air particle movement generated by the leg waving during S. retrorsa courtship may play a role in courtship signalling.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, one review on the impact of ship noise on marine mammals includes a systematic literature search [96]. Two non-systematic reviews can also be cited, one about invertebrates [97] and the other about fishes [98].…”
Section: Reviews and Meta-analysesmentioning
confidence: 99%